Ruthenium–Me-BIPAM-catalyzed addition reaction of aryl-boronic acids to benzofuran-2, 3-diones for the enantioselective synthesis of 3-aryl-3-hydroxybenzofuran-2-ones. Issue 24 (31st December 2015) - Yohda, Masaaki; Yamamoto, Yasunori
Graphical abstract: Abstract: We have developed an enantioselective synthesis of 3-aryl-3-hydroxybenzofuran-2-ones via the ruthenium-catalyzed 1, 2-addition of arylboronic acids to benzofuran-2, 3-diones. The use of RuCl2 (PPh3 )3 with a chiral bidentate phosphoramidite ligand [( R, R )-Me-BIPAM] in the presence of a small amount of acetonitrile (20 mol %) gave optically active 3-aryl-3-hydroxybenzofuran-2-ones with up to 96% ee. This reaction is the first example of a catalytic asymmetric 1, 2-addition reaction of arylboronic acids to benzofuran-2, 3-diones for the highly efficient and enantioselective synthesis of quaternary carbon containing benzofuran-2-ones. Abstract : (3 S )-3-Hydroxy-4, 6-dimethyl-3-phenyl-2, 3-dihydro-1-benzofuran-2-one: C16 H14 O3 Ee = 93% from HPLC [ α ]D 22  = +49.0 ( c 0.50, CHCl3 ) Source of chirality: Asymmetric arylation Absolute configuration: ( S ) Abstract : (3 S )-3-Hydroxy-4, 6-dimethyl-3-(4-phenoxyphenyl)-2, 3-dihydro-1-benzofuran-2-one: C22 H18 O4 Ee = 91% from HPLC [ α ]D 23  = +68.0 ( c 0.50, CHCl3 ) Source of chirality: Asymmetric arylation Absolute configuration: ( S ) Abstract : (3 S )-3-Hydroxy-4, 6-dimethyl-3-(4-methylsulfanylphenyl)-2, 3-dihydro-1-benzofuran-2-one: C17 H16 O3 S Ee = 90% from HPLC [ α ]D 23  = +114.0 ( c 0.50, CHCl3 ) Source of chirality: Asymmetric arylation Absolute configuration: ( S ) Abstract : (3 S )-3-Hydroxy-4, 6-dimethyl-3-(4-methylphenyl)-2, 3-dihydro-1-benzofuran-2-one: C17 H16 O3 Ee = 91% from HPLC [ α ]D 23  = +83.3 ( c 0.54, CHCl3 ) Source of chirality: Asymmetric arylation Absolute configuration: ( S ) Abstract : (3 S )-3-Hydroxy-4, 6-dimethyl-3-(4-phenylphenyl)-2, 3-dihydro-1-benzofuran-2-one: C22 H18 O3 Ee = 91% from HPLC [ α ]D 23  = +69.0 ( c 0.50, CHCl3 ) Source of chirality: Asymmetric arylation Absolute configuration: ( S ) Abstract : (3 S )-3-(4-Chlorophenyl)-3-hydroxy-4, 6-dimethyl-2, 3-dihydro-1-benzofuran-2-one: C16 H13 ClO3 Ee = 95% from HPLC [ α ]D 22  = +86.0 ( c 0.50, CHCl3 ) Source of chirality: Asymmetric arylation Absolute configuration: ( S ) Abstract : (3 S )-3-(4-Fluorophenyl)-3-hydroxy-4, 6-dimethyl-2, 3-dihydro-1-benzofuran-2-one: C16 H13 FO3 Ee = 94% from HPLC [ α ]D 23  = +69.0 ( c 0.50, CHCl3 ) Source of chirality: Asymmetric arylation Absolute configuration: ( S ) Abstract : (3 S )-3-Hydroxy-4, 6-dimethyl-3-(4-(trifluoromethyl)phenyl)-2, 3-dihydro-1-benzofuran-2-one: C17 H13 F3 O3 Ee = 94% from HPLC [ α ]D 23  = +57.0 ( c 0.50, CHCl3 ) Source of chirality: Asymmetric arylation Absolute configuration: ( S ) Abstract : (3 S )-3-(4-Ethenylphenyl)-3-hydroxy-4, 6-dimethyl-2, 3-dihydro-1-benzofuran-2-one: C18 H16 O3 Ee = 94% from HPLC [ α ]D 23  = +63.0 ( c 0.50, CHCl3 ) Source of chirality: Asymmetric arylation Absolute configuration: ( S ) Abstract : (3 S )-3-Hydroxy-3-(naphthalen-2-yl)-4, 6-dimethyl-2, 3-dihydro-1-benzofuran-2-one: C20 H16 O3 Ee = 96% from HPLC [ α ]D 23  = +37.0 ( c 0.50, CHCl3 ) Source of chirality: Asymmetric arylation Absolute configuration: ( S ) Abstract : (3 S )-3-(2 H -1, 3-Benzodioxol-5-yl)-3-hydroxy-4, 6-dimethyl-2, 3-dihydro-1-benzofuran-2-one: C17 H14 O5 Ee = 88% from HPLC [ α ]D 23  = +100.0 ( c 0.50, CHCl3 ) Source of chirality: Asymmetric arylation Absolute configuration: ( S ) Abstract : (3 S )-3-Hydroxy-3-(3, 5-dimethylphenyl)-4, 6-dimethyl-2, 3-dihydro-1-benzofuran-2-one: C18 H18 O3 Ee = 92% from HPLC [ α ]D 23  = +63.0 ( c 0.50, CHCl3 ) Source of chirality: Asymmetric arylation Absolute configuration: ( S ) Abstract : (3 S )-3-Hydroxy-3-(3-chlorophenyl)-4, 6-dimethyl-2, 3-dihydro-1-benzofuran-2-one: C16 H13 ClO3 Ee = 94% from HPLC [ α ]D 23  = +64.0 ( c 0.50, CHCl3 ) Source of chirality: Asymmetric arylation Absolute configuration: ( S ) Abstract : (3 R )-3-(2-Fluorophenyl)-3-hydroxy-4, 6-dimethyl-2, 3-dihydro-1-benzofuran-2-one: C16 H13 FO3 Ee = 87% from HPLC [ α ]D 24  = −135.0 ( c 0.50, CHCl3 ) Source of chirality: Asymmetric arylation Absolute configuration: ( R ) Abstract : (3 S )-3-Hydroxy-3-phenyl-4, 7-dimethyl--2, 3-dihydro-1-benzofuran-2-one: C16 H14 O3 Ee = 93% from HPLC [ α ]D 23  = +57.0 ( c 0.50, CHCl3 ) Source of chirality: Asymmetric arylation Absolute configuration: ( S ) Abstract : (3 S )-5-Bromo-3-hydroxy-4, 6-dimethyl-3-phenyl-2, 3-dihydro-1-benzofuran-2-one: C16 H13 BrO3 Ee = 94% from HPLC [ α ]D 23  = +86.0 ( c 0.50, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( S ) Abstract : (3 S )-3-Hydroxy-4-methyl-3-phenyl-2, 3-dihydro-1-benzofuran-2-one: C15 H12 O3 Ee = 92% from HPLC [ α ]D 23  = +29.0 ( c 0.50, CHCl3 ) Source of chirality: Asymmetric arylation Absolute configuration: ( S )